A Chimeric NaV1.8 Channel Expression System Based on HEK293T Cell Line - Zhou, Xi; Zhang, Yunxiao; Tang, Dongfang; Liang, Songping; Chen, Ping; Tang, Cheng; Liu, Zhonghua (Frontiers in Pharmacology, 2018)
Among the nine voltage-gated sodium channel (NaV) subtypes, NaV1.8 is an attractive therapeutic target for pain. The heterologous expression of recombinant NaV1.8 currents is of particular importance for its electrophysiological and pharmacological studies. However, NaV1.8 expresses no or low-level functional currents when transiently transfected into non-neuronal cell lines. The present study aims to explore the molecular determinants limiting its functional expression and accordingly establish a functional NaV1.8 expression system. We conducted screening analysis of the NaV1.8 intracellular loops by constructing NaV chimeric channels and confirmed that the NaV1.8 C-terminus was the only limiting factor. Replacing this sequence with that of NaV1.4, NaV1.5 or NaV1.7 constructed functional channels (NaV1.8/1.4L5, NaV1.8/1.5L5 and NaV1.8/1.7L5, respectively), which expressed high-level NaV1.8-like currents in HEK293T cells. The chimeric channel NaV1.8/1.7L5 displayed much faster inactivation of its macroscopic currents than NaV1.8/1.4L5 and NaV1.8/1.5L5, and it was the most similar to wild-type NaV1.8 expressed in ND7/23 cells. Its currents were very stable during repetitive depolarizations, while its repriming kinetic was different from wild-type NaV1.8. Most importantly, NaV1.8/1.7L5 pharmacologically resembled wild-type NaV1.8 as revealed by testing their susceptibility to two NaV1.8 selective antagonists, APETx-2 and MrVIB. NaV chimeras study showed that at least the domain 2 and domain 4 of NaV1.8 were involved in binding with APETx-2. Our study provided new insights into the function of NaV1.8 intracellular loops, as well as a reliable and convenient expression system which could be useful in NaV1.8 studies.